Spacing effect on growth and yeld of fast rotation Eucalyptus at 24 months of age (Research, Society and Development, 2020)
The objective of this study was to evaluate the growth in height, diameter and volume production of a eucalyptus clone at 24 months of age planted at different spacing. Values of circumference at soil height, circumference at chest height and the heights of all plants in the plots were collected at 6, 12, 18 and 24 months after planting. Using the collected data, the diameter values at ground and chest height and the mean height at each age were calculated. Rigorous cubing of the average tree in each plot was performed 24 months after planting to obtain the wood volume per tree and per hectare. The spacing did not present a clear pattern of influence on the total height of the plants. The final height was not affected by spacing. The effect of planting spacing on growth in diameter at soil height intensified from the first year after planting. Tree mean diameter increased with planting spacing, as well as the wood volume per tree. Wood volume per hectare was higher in the denser spacing.